Menelusuri Dinamika Sejarah Pendidikan Islam di Barus - Badruddin; Zulfiqri, Muammar (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2024)
This research aims to detail the Islamic journey in the city of Barus with the aim of understanding the development of Islam in the territory of Nusantara. On March 24, 2017, the Government of the Republic of Indonesia officially designated the city of Barus as the zero-point monument of the center of Nusantara Islamic civilization. The research methods used are qualitative, with historical approaches, criticism, and interpretation. The researchers used the following scheme: first, evaluate historical information sources related to Islamic history in Barus, then carry out analysis, criticism, and interpretation of such information. The results will reveal the role of Barus as the starting point for the spread of Islam in Nusantara, followed by its spread to other regions such as Peureulak and Pasai. Although Barus accepted Islam early, the territory did not form a power or Islamic empire that had political power.